ЗАХОДИ ЗАБЕЗПЕЧЕННЯ ПРОКУРОРОМ ЦИВІЛЬНОГО ПОЗОВУ В КРИМІНАЛЬНОМУ ПРОВАДЖЕННІ - Коваленко, Андрій Олександрович (SUPREMANCE OF LAW, 2017)
The article is devoted to theoretical questions of application of measures of maintenance by the public prosecutor of the civil claim in criminal manufacture. Particular attention is paid to the ratio of measures to ensure criminal proceedings and measures of criminal procedure coercion. It is indicated that measures to ensure civil action is a form of criminal procedural enforcement measures and refer to compulsory measures to ensure criminal proceedings.
Keywords: measures to ensure criminal proceedings; civil action; temporary access to things and documents; temporary seizure of property; seizure of property